Development of synthetic biology tools by methods in silico and in vivo applied to bacteria of biotechnology importance - Rojas, Maria Juliana Rolon (2020)
In spite of the enormous scientific and biotechnological advances achieved by Synthetic Biology in the last decades, one of the great limitations in its development consists of the low diversity of standard biological parts (qualitatively and quantitatively characterized) that allow the construction of complex synthetic circuits. In this context, the increasing number of sequenced bacterial genomes, the bioinformatic tools and the advancement of molecular techniques allow the exploitation of these systems. Such an approach allows the exploration of the diverse genetic elements to create orthogonal synthetic tools bio-inspired in microorganisms that have evolved for containing in their genomes genetic elements that could be useful for biotechnological purposes. One of the most remarkable microorganisms that fit with this description is Pseudomonas putida, due to its great plasticity and tightly transcriptional control which allow it to degrade more than 100 aromatic compounds derived from lignin. Thus, in the present work, new tools for the analysis of transcriptional factors (TFs) with their cis-regulatory elements were designed, which resulted in four new vectors with validation capacity in a large number of different bacteria species based on pSEVA plasmids family architecture; with reporter systems containing the proteins sGFP (super folding green fluorescent protein), mCherry and degradation tags adjustable with the growth temperature of each microorganism. Also, we studied an in silico approach modelling proteins by threading in TF from the genome of Pseudomonas putida and then, we perform a molecular docking using the major aromatic compounds that have been reported in the literature as degraded by this bacteria. This result in the selection of candidates proteins from the MarR family PP_3359, VanR which response to molecules of the degradation pathway to Ferulic acid; And the protein GalR, LysR type regulator which responds Galic Acid and homologues in order to create tools for synthetic biology-inspired by natural systems for biotechnological applications.